USO DEL ELISA DE CAPTURA DE ANTÍGENO EN EL MONITOREO DE PORCINOS INFECTADOS NATURALMENTE CON Cysticercus cellulosae Y TRATADOS CON OXFENDAZOL - Tinoco F., Yeny (2004)
Taenia solium cysticercosis is a serious public health problem in developing countries around the world. At the present time, treatment with anthelmintic drugs is possible, but once applied the treatment the monitoring of the animal is limited by the high cost of the radiological techniques. Moreover, the available immunodiagnostic assays are not useful for monitoring because they detect the presence of antibodies against C. cellulosae, which remain in circulation after cysts are dead. The objective of the present study was to demonstrate the usefulness of a monoclonal antibody-based capture ELISA (AgELISA) in the monitoring of the persistence of circulating parasite antigens in animals treated against cysticercosis. For this purpose, serum samples corresponding to the monitoring of pre and post treatment of 6 pigs, naturally infected with cysticercosis and treated with oxfendazol, were evaluated. Necropsy data and evagination records were also used. It was found that the time in which the antigen titles were lower to the cut off OD values occurred on day 59 post treatment and that the mean survival time was 71.5 (59.3-83.8) days. These results seem to demonstrate that the Ag-ELISA would allow the quantitative monitoring of the behavior and persistence of circulating antigens in naturally infected animals that are treated with an antiparasitic drug. However, the monitoring of additional treated pigs are required to obtain conclusive results.